Consumption and Welfare in Ghana in the 1990s. - Teal, F (Routledge, 2006)
In this paper two issues, which have been the subject of much multidisciplinary research, are investigated. The first is whether consumption expenditure can be treated as a measure of welfare. The second is whether larger households can be viewed as richer than smaller ones. These issues are investigated drawing on data for Ghana covering the 1990s. It is argued that while household consumption can act as an opportunity measure of welfare the use of averages can mislead. The problems in assessing how household size affects the measurement of welfare are discussed in the context of Ghana's experience of poverty reduction.